ESTIMATION OF FINANCIAL STABILITY OF AGRARIAN ENTERPRISES IN UKRAINE - Nadia Davidenko; Natalia Wasilewska (Polityki Europejskie, Finanse i Marketing)
In this paper the system of factors influencing the formation of financial solvency was investigated, the financial sustainability of agricultural enterprises of Ukraine was evaluated, and an approach was developed to define and help ensure the financial sustainability of enterprises in the face of contemporary economic and market challenges. According to the research, the main principles for maintaining financial sustainability are: responsiveness to internal and external changes; governance systems; risk management; analysis of financial ratios; real assessment of the financial solvency of the enterprise; integration with the overall management system; orientation towards achieving the strategic goals of the enterprise; use of qualitative methods to inform financial decisions in the face of uncertainty and risk.